Impact of fast advancement and early fortification of enteral feedings in preterm infants, a retrospective, observational study - Gomez-Pomar, Enrique; Clarke, Holly; Adams, Jamie (Frontiers in Pediatrics, 2025)
We aimed to evaluate the outcomes and growth of preterm infants at a Neonatal Intensive Care Unit that focuses on early initiation, fast advancement, and early fortification of enteral feeds.MethodsRetrospective study conducted at a community hospital level III NICU. Extensive feeding data and outcomes were collected by utilizing a NutritionIQ software application, NICUtrition®. Infants born between 26- and 34-weeks gestational age were included, whereas infants with congenital defects, deceased or with incomplete data were excluded. Frequency and descriptive statistical analysis were conducted using chi-square and Fisher's exact test. Unadjusted odds ratios were computed for categorical variables and general linear models were conducted to adjust for covariates (birth weight and gestational age) in sensitivity analyses.ResultsA total of 297 preterm infants were included. On average, infants reached target enteral feeds of at least 120cc/kg/day and received fortification by day 6 of life. Achievement of target enteral feeds within the first week of life was associated with improved delta z-scores for weight and length as well as significantly less rates of sepsis. Infants that achieved target enteral feedings and fortification during the first week of life were associated with significantly improved delta z-scores for weight, length, and head circumference. Contrary to expectations, the use of Mother's Own Milk alone was not associated with improved outcomes.ConclusionsThis study highlights the association of early initiation, faster advancement and fortification of enteral feedings on preterm infants. These interventions improved growth metrics (weight, head circumference, and length z-scores) and were associated with decreased prevalence of sepsis.